Chronic crisis management: the perception of Malay managers in Malaysian business organization - Fontaine, Rodrigue Ancelot Harvey (International Islamic University Malaysia, 2012)
This study investigates crisis management by focusing on Bohn (2000). Bohn (2000) uses the term ‘fire fighting’ to describe firms that are in a chronic state of crisis management. Typically, managers rush from one problem to another without having the time to solve problems effectively. They often deal with symptoms but fail to address the root causes of the problem. Fire fighting arises because of a) weaknesses in individual problem-solving skills, b) dysfunctional team dynamics and c) systems problems within the organization. This study explores chronic crisis management in Malaysia by surveying the perception of 150 Malay managers using an instrument derived from the literature. By and large, the data confirms the literature review. The implications for management from an Islamic perspective (MIP) are discussed. In particular, this author speculates that MIP can help develop a better organizational culture and a process-orientated management approach. Both would help prevent fire fighting in organizations.